T1ρ Magnetic Resonance Imaging to Assess Cartilage Damage After Primary Shoulder Dislocation. Issue 3 (23rd March 2015) - Saxena, Vishal; DAquilla, Kevin; Singh, Anup; Gordon, Joshua Asher; Fenty, Matthew; Carey, James L.; Borthakur, Ari; Kneeland, John Bruce; Reddy, Ravinder; Sennett, Brian J.
Objectives: Anterior shoulder dislocation is a common injury with an estimated incidence of 23.1/100, 000 person-years. In anterior dislocation, associated injuries typically involve the anteroinferior glenoid and posterosuperior humeral head. Patients who suffer a shoulder dislocation are at higher risk of developing glenohumeral arthropathy; the risk increases with recurrent dislocations. However, little is known about the initial cartilage damage after a primary shoulder dislocation. T1ρ is a magnetic resonance imaging (MRI) modality that allows quantification of cartilage proteoglycan content and can be used to detect physiologic changes in cartilage without intravenous contrast. Cartilage degeneration is characterized by decreased proteoglycan content, which results in an increased T1ρ relaxation constant. T1ρ MRI can detect differences in knee cartilage between Kellgren-Lawrence grades as well as acetabular cartilage changes in patients with femoroacetabular impingement. The objectives of this prospective study were to determine if T1ρ MRI can detect cartilage damage following primary shoulder dislocation and to assess for patterns in cartilage damage in anterior dislocations. Methods: This study received Institutional Review Board approval. Nine patients (mean age 31.3 years, range 20-59) who had sustained anterior shoulder dislocations underwent a 3T T1ρ MRI within ten days of their injury. Five control patients without prior dislocation or glenohumeral arthritis also underwent 3T T1ρ MRI. The T1ρ relaxation constant was determined for the entire glenoid and humeral head for dislocation and control patients. In addition, the glenoid was divided into nine zones, and T1ρ values were determined for each zone in dislocated and control patients to assess for differences between the two groups and to identify any patterns in cartilage damage in dislocated patients. Results: T1ρ mapping of glenohumeral cartilage in dislocated shoulders showed significant cartilage damage. Overall T1ρ values were increased in dislocated shoulders compared to control shoulders for glenoid and humeral head cartilage (53.46±0.99 vs. 36.60±3.6 and 46.50±1.1 vs. 36.19±1.7, respectively; mean±SEM, p = 0.0025, Fig. 1A). Furthermore, T1ρ values were significantly increased in all glenoid zones in dislocated shoulders compared to controls except for posterior/inferior (p = 0.064 for posterior/inferior, p < 0.02 for all other zones, Fig. 1B). However, there were no significant differences in T1ρ values between glenoid zones in dislocated shoulders across patients, reflecting widespread cartilage damage. Conclusion: T1ρ MRI is sensitive for detecting cartilage damage and proteoglycan loss after shoulder dislocation. T1ρ values were significantly higher (lower proteoglycan content) in nearly all glenoid zones in dislocated shoulders compared to controls and approached significant difference in the posterior/inferior zone. Although the anteroinferior glenoid and posterosuperior humeral head are characteristically affected in anterior dislocation, cartilage damage was surprisingly more widespread and affected the entire joint. The etiology of diffuse cartilage damage is unknown but may be due to hemarthrosis or additional trauma to the joint during humeral head relocation. Longer-term studies are needed to determine if the initial cartilage damage persists and if cartilage damage worsens with repeat dislocations.